QUASI AND REAL TOUGHENING OF CRIMINAL LIABILITY FOR MEDIATION OF BRIBERY - E. V. Rogova; R. A. Zabavko (Russian Journal of Economics and Law)
Objective: to identify the disputable issues of criminal-legal regulation and problems of criminal law norms application, establishing liability for mediation in bribery. Basing on the analysis, to propose ways to resolve some of them.Methods: for the accuracy and completeness, general and special methods of scientific cognition were applied. The general methods include historical-legal, logical-legal, comparative legal methods, systemic analysis and synthesis. Special methods are study of documents and content analysis; expert evaluation method.Results: the authors came to a conclusion about the need to reform the law concerning the criminal liability for mediation in bribery. One of the solutions to the problem is to change the disposition of Article 291.1 of the Criminal Code. However, a comprehensive analysis of the problems of application of this regulation and the norms of the General part of the Criminal Code indicates that there is no need to legislatively confirm the criminal liability for mediation in bribery.Scientific novelty: the complex analysis of problems of the application of Article 291.1 of the RF Criminal Code has been made, which serves as the basis to justify the inconsistency of this provision of the criminal law; a proposal is made to make amendments in the norms of the General part of the Criminal Code of the Russian Federation relating to the concept of accomplice of the crime.Practical significance: the results can be used in the reforming of criminal legislation of the Russian Federation, and also at the further research of problems of differentiation of liability for bribery.